(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
In the recent years, Data has increased exponentially and is termed as Big Data. Data Amount, Data Speed and Data Variation are three major parameters of Big Data. There are many challenges which have tuned up out of which Data Storage, Data Analysis and Data Management are the biggest ones. In order to deal with these challenges, Machine Learning, a subset of Artificial Intelligence provides various tools and techniques. This paper gives a detail about Big Data and Machine Learning. It also includes detailed literature review on various Big Data case studies which are solved by Machine Learning Techniques.